Development of Ethnoscience-based Science Booklet Integrated with Islamic Values in Science Learning in Junior High Schools - Syafira, Annisa; Yuliastrin, Adisti; Susilawati, Susilawati; Vebrianto, Rian (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
This research aims to create an ethnoscience-based science booklet media integrated with Islamic values to teach science to junior high school students. This research uses the ADDIE model development stage with a research instrument in the form of a questionnaire involving 4 expert validators, 20 prospective teachers, and students. The product to be developed is an ethnoscience-based science booklet media with earth and solar system material that can be used by junior high school (SMP). The validity test results in terms of language aspects amounted to 78.3%, material aspects to 84%, design aspects to 84%, and visual display aspects to 75%. All aspects of the validity test were classified as very valid. The reliability test obtained a result of 0.667, categorized as reliable, and the practicality test obtained a value of 87.71%, classified as very practical. The novelty of this research is that researchers combine cultural and scientific knowledge in the form of booklet science media and are also integrated with Islamic values. So, it can be concluded that the ethnoscience-based science booklet media integrated with Islamic values is valid, reliable, and practical so that junior high schools can use it.